Haida village and totem poles, Klinkwan, Alaska, ca. 1906. - Hunt, Mrs. Forrest
On verso of image: Photo by Mrs. Forrest Hunt, Ketchikan. Copied by William Hagevig, 1951 Note from unidentified source: Klinkwan village, S. E. Alaska. Houses and poles viewed from water. In Garfield Volume 1, leaf 75